Organizational cynicism and employee turnover intention: Evidence from banking sector in Pakistan - Muhammad Arsalan Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The idea of the research study is to examine the effect of organizational cynicism (OC) on employee turnover intention (TI). The literature on organizational cynicism and turnover intention demonstrates that cynicism has profound effects on turnover intention. Further the influence of job satisfaction (JS) and intrinsic motivation (IM) as mediating variables were also investigated. The data was gathered through self-administered questionnaire from 250 employees functioning on various positions in domestic private sector banks from two cities of Pakistan (Rawalpindi/Islamabad). The findings of survey concluded that Job satisfaction and intrinsic motivation partially mediates the relationship between organizational cynicism and turnover intention. The main limitation of the study is the sample used, that is from the banking segment and from twin cities (Rawalpindi/Islamabad). Self-reported questionnaire data is use as the medium of measurement in the present study. To cope with the challenge management must create an atmosphere within the banks to improve employees' intrinsic motivation to reduce turnover intention. This study may contribute to the knowledge available on cynicism an area that is almost under-research in Pakistan.
Keywords: 330; organizational cynicism; Job satisfaction; intrinsic motivation; turnover intention